TAKING THE LONELY WALK IN IRAQ AND AFGHANISTAN - Beukes, T. (Scientia Militaria - South African Journal of Military Studies, 2014)
Eight lives down, Extreme risk and Bomb hunters all contain the personal accounts of British soldiers who served as bomb-disposal operators during the recent armed conflicts in Iraq and Afghanistan. The books were not written as scholarly works intended for an academic audience. Serious students of contemporary armed conflict nevertheless would find them useful reading material. The books should be particularly useful to scholars with a professional interest in asymmetric warfare or the emerging role of improvised explosive devices in contemporary armed conflict.